Digital nuclear shell model - Kuric, Lutvo (International letters of chemistry, physics and astronomy, 2014)
The subject of this thesis is a digital approach to the investigation of the digital basis of digital nuclear shell model. The shell model is partly analogous to the atomic shell model, which describes the arrangement of electrons in an atom, in that a filled shell results in greater stability. In a three-dimensional harmonic oscillator the total degeneracy at level n is ... Due to the spin, the degeneracy is doubled and is (n+1)(n+2). Thus the magic numbers would be ... for all integer k. The digital mechanism of shell model have been analyzed by the application of cybernetic methods, information theory and system theory, respectively. This paper is to report that the author discovered new methods for development of the new technologies in nuclear physics and chemistry. It is about the most advanced digital technology which is based on program, cybernetics and informational systems and laws. The results in practical application of the new technology could be useful in physics, chemistry, bioinformatics, and other natural sciences.(ProQuest: ... denotes formulae/symbols omitted.)